2010
DOI: 10.1523/jneurosci.0022-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectory of Object Recognition Memory in Infant Rhesus Macaques with and without Neonatal Hippocampal Lesions

Abstract: To examine the developmental trajectory of object recognition memory and its neural substrate, 10 -12-d-old monkeys (Macaca mulatta) receivedshamoperationsorneurotoxichippocampallesionsandweretestedattheagesof1.5,6,and18monthsonthevisualpaired-comparison task using delays of 10, 30, 60, and 120 s. In sham-operated controls, incidental recognition memory was present at 1.5 months, became more robust at 6 months, and was delay-dependent by 18 months of age, suggesting that the brain structures mediating these ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(128 citation statements)
references
References 50 publications
11
117
0
Order By: Relevance
“…Indeed, provided the pictures used are dissimilar, VPC leads to the same conclusion as DNMS: Recognition memory is spared by selective hippocampal lesions and color is not the determinant factor for such VPC sparing to occur as it is equally present with dissimilar BW pictures with gray shading replacing colors. This conclusion is strengthened by our recent results that animals with hippocampal lesions in the present study with spared recognition memory in VPC with dissimilar color and BW pictures also showed spared performance when subsequently tested on DNMS (Heuer and Bachevalier 2010).…”
Section: Vpc Vs Dnms: Narrowing the Gapsupporting
confidence: 84%
“…Indeed, provided the pictures used are dissimilar, VPC leads to the same conclusion as DNMS: Recognition memory is spared by selective hippocampal lesions and color is not the determinant factor for such VPC sparing to occur as it is equally present with dissimilar BW pictures with gray shading replacing colors. This conclusion is strengthened by our recent results that animals with hippocampal lesions in the present study with spared recognition memory in VPC with dissimilar color and BW pictures also showed spared performance when subsequently tested on DNMS (Heuer and Bachevalier 2010).…”
Section: Vpc Vs Dnms: Narrowing the Gapsupporting
confidence: 84%
“…In particular, we think that the novelty of the material to be remembered and the higher information load demand in our task, as compared with the odor span task, which proportionally loaded the object working memory system, allowed us to find an effect of HP lesion (Kumaran and Maguire 2007). Furthermore, it has been recently shown that neonatal hippocampus selective lesion in monkeys strongly impairs adulthood novel object recognition in a nonassociative task (incidental learning task based on spontaneous preference for novel objects) (Zeamer et al 2010), but did not affect it when animals are trained to respond to novelty upon instrumental contingency (Heuer and Bachevalier 2011). This suggests that the nonassociative nature of our task, which makes it quite close to incidental learning in humans and monkeys, might have favored the recruitment of the HP in the object task.…”
Section: The Dorsal Hippocampus Mediates Object Stm In High Memory Lomentioning
confidence: 86%
“…Using these tasks, novelty preference has been demonstrated following short-term retention periods (Bachevalier and Nemanic, 2008;Pascalis and de Schonen, 1994;Jutras and Buffalo, 2010;Zeamer et al, 2010) in both human infants and monkeys. A number of studies have also documented novelty preference following long-term retention intervals (Gunderson and Swartz, 1985;Pascalis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%